Microstructure and properties of nickel- titanium alloy manufactured by twin- wire arc additive manufacturing - ZHAO Huayu; HUANG Jiankang; XIANG Rui; ZHAO Tianxiang; XU Jianzhou; SONG Xueping; FAN Ding (Cailiao gongcheng)
In order to obtain NiTi alloy with excellent properties， dual-wire arc additive manufacturing technology is used to control the wire feed speed of Ni and Ti wires， and precisely adjust the atomic ratio and phase composition of Ni alloy. The results show that when the Ni/Ti atomic ratio is 8∶10 in the center of the longitudinal cladding passage， the deposited NiTi alloy is mainly composed of Ti2Ni phase accompanied by a small number of Ti-rich particles， and the microhardness and compressive strength reach 560HV and 1600 MPa， respectively. When the Ni/Ti atomic ratio is 11∶10， the Ti2Ni phase is included in the NiTi phase， and the irrecoverable strain of 1.6% appears in the cyclic compression process. When the atomic ratio of Ni/Ti is 15∶10， the cluster Ni3Ti phase is formed in the NiTi phase， the longitudinal fracture strain is close to 40%， and the irrecoverable strain is only 1.2% after cyclic compression， showing good superelasticity. In addition， compared with the central region of the longitudinal cladding passage， the microstructures of the transverse lapping region of the samples with different Ni/Ti atomic ratios show obvious grain coarsening and component segregation， and the compressive strength and plastic deformation ability are significantly reduced.